إجراء العقود بوسائل الاتصال المستحدثة في ضوء الفقه الإسلامي: Concluding Contracts by Modern Means of Communication: An Islamic Jurisprudence Perspective - hikmah, admin; Saising, Hanif (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2026)
ملخص البحث تستعرض هذه الدراسة إحدى أهم النوازل الفقهية المعاصرة المتمثلة في "التعاقد عن بُعد" عبر وسائل الاتصال التقني، مستهدفةً بيان التكييف الفقهي لمجلس العقد الحكمي ومدى مواءمته للأصول الشرعية. تكمن إشكالية البحث في مدى تحقق الركنية والشرائط الشرعية كالاتحاد في المجلس، والارتباط بين الإيجاب والقبول في ظل غياب المشافهة والحضور البدني المتعارف عليه في الفقه الإسلامي. اعتمد البحث على المنهج الاستقرائي التحليلي لمراجعة النصوص الشرعية وما يلحق بها من ضوابط فقهية وقواعد كلية ذات الصلة، مع إسقاطها على الواقع التقني المعاصر. وخلصت الدراسة إلى أن إجراء العقود عبر الوسائل الحديثة ينسجم مع مقاصد الشريعة القائمة على تيسير المعاملات وجلب المصالح، شريطة استيفاء العقد لأركانه من عاقدين، ومعقود عليه، وصيغة، مع مراعاة الضوابط الخاصة بـخيار المجلس والتحقق من أهلية المتعاقدين وسلامة الإرادة التعاقدية من الغرر والتدليس. كما أثبت البحث توافق هذه الوسائل مع القرارات الصادرة عن المجامع الفقهية العالمية كمجمع الفقه الإسلامي الدولي، التي أقرت بصحة هذه العقود بناءً على قاعدة "العبرة في العقود للمقاصد والمعاني لا للألفاظ والمباني". وفي الختام، أوصى البحث بضرورة صياغة أطر قانونية وتشريعية لتنظيم التجارة الإلكترونية، بما يضمن حقوق الأطراف ويدعم عجلة التنمية الاقتصادية في ظل التحول الرقمي العالمي. ABSTRACT This study examines one of the most prominent contemporary jurisprudential issues, namely "Remote Contracting" through modern technological communication. It aims to provide a jurisprudential characterization of the "Constructive Contractual Session" and evaluate its alignment with Islamic legislative principles. The research problem centers on the fulfillment of essential pillars and Sharia conditions—such as the unity of the session and the nexus between offer and acceptance—given the absence of oral communication and physical presence customary in classical jurisprudence. The research adopts an inductive-analytical methodology to review Sharia texts, associated jurisprudential controls, and universal maxims, applying them to the contemporary technological landscape. The study concludes that concluding contracts via modern means aligns with the Higher Objectives of Sharia intended to facilitate transactions and secure public interests. This is contingent upon the contract fulfilling its essential pillars: the contracting parties, the subject matter, and the legal formula, while observing specific controls regarding the "Option of the Session", verifying the legal capacity of the parties, and ensuring the integrity of contractual intent against uncertainty and deception. Furthermore, the research demonstrates the compatibility of these digital means with resolutions issued by international Fiqh academies, such as the International Islamic Fiqh Academy, which affirmed the validity of such contracts based on the legal maxim: "In contracts, regard is given to intentions and meanings, not to words and structures." In conclusion, the research recommends the formulation of robust legal and legislative frameworks to regulate e-commerce, thereby ensuring the rights of all parties and supporting economic development amidst the global digital transformation.